Wideband textile antenna for WLAN and WIMAX applications - Ahmed Yusuf, Farhan (2021)
Antennas that available in the industry have designed for one purpose application with narrow band which makes the system functions with more than one antenna with a narrow band. Additionally, most existing wideband antennas are not flexible since it uses traditionally rigid material that make them uncomfortable to the user. Therefore, a new technology becomes necessary by designing wideband textile antenna with flexible substrates and cost efficiency. The substrate of the designed antennas is made from denim textile material with size of 45x70 mm, while radiating element and partial ground plane are made from copper tape with circular patch radius of 20.9 mm and feed line of 2.9x20.3 mm. The partial ground has a size of 40x19.65 mm in the lower part of the antenna. The patch has two feed slots with size of 2.80x2.99 mm and in the middle of the circular the is square diamond with size of 8.90 mm and upper square diamond with of 5.49 mm. The design is used both CST and validated by HFSS. The operating frequency of the design is from 2 to 4 GHz with reflection coefficient of - 29.346 dB. It has a gain of 2.378 dB at 2.45 GHz and 3.453 dB at 3.5 GHz. Validated results are compared with CST simulations and acceptable agreement was observed. Furthermore, in this project was analyzed the bending effect of the antenna with radius from 10 to 125 mm and its SAR. The SAR value of the antenna was tested, based on flat and bended antenna to show the radiation effect on the human body phantom, in the case of flat antenna the SAR value is 1.255 W/kg at 2.45 GHz and 1.302 W/kg at 3.5 GHz. Nevertheless, the bended SAR value shows 1.68 at 2.45 GHz and 1.88 W/kg at 3.5 GHz. The SAR values of both antennas are safe according to the International Commission on Non-Ionizing Radiation Protection (ICNIRP, European standard). The safe level for the standard is 2 W/kg for any 10 grams of tissue.